PENERAPAN DINAMIKA ALAMIAH PADA LAGU-LAGU YANG TIDAK BERTANDA DINAMIKA - R.A. Dinar Sri Hartati (Institut Seni Indonesia Yogyakarta, 2012)
Music is expression in sound. Sound without expression is not music. In music we express the idea. Dynamic is a musical elemen, that has function to express the idea and the soul of the sound, so the sound can be music. This article gives a practical direction about how we can applicate dynamic in a musical composition naturally so the idea of music can we hear, feel, and enjoy. Keywords: Dynamic, Music, Composition